CAN EXCHANGE RATE CONTROL IN TURKEY HELP THE CENTRAL BANK EVALUATIONS WITHIN THE FRAMEWORK OF THE TAYLOR RULE - Özek, Yavuz; Ergür, Halil Oğuzhan (My University, 2024)
This paper tests the validity of the Augmented Taylor rule in the Turkish economy for the period between February 2011 and February 2024 with the structural vector autoregression model. It is found that the central bank did not use the policy rate against deviations from inflation in the relevant period. On the other hand, the policy rate moves within expectations against deviations in the output gap and the real exchange rate. According to the structural impulse-response functions, the output gap and the inflation gap respond positively to a one-unit shock to the policy rate, while the real exchange rate reacts negatively. According to the results of structural variance decomposition, the most influential variable on changes in the policy rate is the real exchange rate deficit. In conclusion, the policy rate in the Turkish economy takes into account the output gap and the real exchange rate gap. However, it ignores the inflation gap.
Keywords: Exchange rate; augmented taylor rule; structural var model